Laminated Aluminum Foil Insulator Experiment With Noise Shielding Capability For Myoelectric Signal Socket Processing Device - Quraish Quraish; Susy Susmartini; Ilham Priadythama (Performa: Media Ilmiah Teknik Industri, 2014)
This research investigates the problem of electromagnetic noise on myoelectric device. This myoelectric device has a low pass filter response (Butterworth type) with cut-off frequency (fc) 6 Hz and passing 8 volt signal. The passed signal, then amplified by a differential amplifier for 150 times into 1,2 Volt (20% noise captured system). So we require an approach to electromagnetic shielding to reduce interference from the outside that enter into the device system. In this study utilizing an experimental design using full factorial experiment methods to determine the effect of the type of bahan, the frequency response, and the interaction to the performance of shielding. The experiment results showed that each element and their interactions, significantly affected the value of the shielding performance. Aluminium foil air cell bubble has the highest shielding performance with the average performance of shielding efficiency of 94,80887 %. This bahan used for shielding socket design proposal which based in the Wisconsin department of health service and American heart association standard.